Growth and development across the lifespan a health promotion focus - Leifer, Gloria (Elsevier, 2013)
Provides introductory coverage of growth and development throughout the lifespan. This title emphasizes normal aspects as well as the problems and health promotion needs of each age and stage of development. It features a health promotion theme structured around "Healthy People 2020" objectives.